Developing a new quality of life instrument with older people for economic evaluation in aged care: study protocol. Issue 5 (24th May 2019) - Ratcliffe, Julie; Cameron, Ian; Lancsar, Emily; Walker, Ruth; Milte, Rachel; Hutchinson, Claire Louise; Swaffer, Kate; Parker, Stuart
Abstract : Introduction: The ageing of the population represents a significant challenge for aged care in Australia and in many other countries internationally. In an environment of increasing resource constraints, new methods, techniques and evaluative frameworks are needed to support resource allocation decisions that maximise the quality of life and well-being of older people. Economic evaluation offers a rigorous, systematical and transparent framework for measuring quality and efficiency, but there is currently no composite mechanism for incorporating older people's values into the measurement and valuation of quality of life for quality assessment and economic evaluation. In addition, to date relatively few economic evaluations have been conducted in aged care despite the large potential benefits associated with their application in this sector. This study will generate a new preference based older person-specific quality of life instrument designed for application in economic evaluation and co-created from its inception with older people. Methods and analysis: A candidate descriptive system for the new instrument will be developed by synthesising the findings from a series of in-depth qualitative interviews with 40 older people currently in receipt of aged care services about the salient factors which make up their quality of life. The candidate descriptive system will be tested for construct validity, practicality and reliability with a new independent sample of older people (n=100). Quality of life state valuation tasks using best worst scaling (a form of discrete choice experiment) will then be undertaken with a representative sample of older people currently receiving aged care services across five Australian states (n=500). A multinomial (conditional) logistical framework will be used to analyse responses and generate a scoring algorithm for the new preference-based instrument. Ethics and dissemination: The new quality of life instrument will have wide potential applicability in assessing the cost effectiveness of new service innovations and for quality assessment across the spectrum of ageing and aged care. Results will be disseminated in ageing, quality of life research and health economics journals and through professional conferences and policy forums. This study has been reviewed by the Human Research Ethics Committee of the University of South Australia and has ethics approval (Application ID: 201644).